Pengaruh gaya hidup konsumtif terhadap moral remaja - Maisaroh, Putri Nur Kholishoh (Maliki Interdisciplinary Journal, 2024)
The development of globalization creates many phenomena and has various impacts on humans in real life. One example is the creation of a wasteful lifestyle that affects the morals of society, especially among teenagers. This is due to the pattern of social interaction among adolescents influenced by globalization, namely patterns of interaction that use attributes or symbols to show their self-image. Thus, many teenagers change themselves to be accepted in social groups. Many think buying branded, glamorous and contemporary goods will take them by these groups. Without realizing it, this consumptive lifestyle hurts the morale of teenagers. One example is that teenagers will be lazy, wasteful, and don’t care about the future. In addition, the extravagant culture of life is also contrary to Pancasila’s morality.